FAKTOR-FAKTOR ANEMIA PADA IBU HAMIL DI PUSKESMAS SINDANG BARANG KOTA BOGOR TAHUN 2023 - Ariandini, Shanti (Universitas Muhammadiyah Surabaya, 2024)
Objective: This study aims to measure the incidence of anemia in pregnant women and study factors related to anemia in pregnant women in the work area of ​​the Sindang Barang Community Health Center, Bogor City in 2023 Methods: The research methodology used was cross-sectional. The population was 407 people, with a sample of 110 /pregnant women. The research results showed a figure of 55.5% (95% CI: 47%-67%).%). These findings indicate that the proportion of anemia remains high in the Sindang Barang Community Health Center working area. Results: In this study, indirect causal factors related to the incidence of anemia in pregnant women were the mother's age, gestational age, and the number of blood supplement tablets consumed. This research also found fundamental factors related to the incidence of anemia in pregnant women, namely education and family income Conclusion: It is recommended that the role of community health center midwives be to provide counseling and promotion of anemia prevention. Cadre activity is needed as a facilitator to monitor compliance with taking blood supplement tablets